AB0014 Implication of VEGFR2 in systemic lupus erythematosus: A combined genetic and structural biological approach. (23rd January 2014) - Zervou, M.I.; Eliopoulos, E.; Vazgiourakis, V.; Sharma, S.; Sidiropoulos, P.; Franek, B.S.; Myrthianou, E.; Melissourgaki, M.; Niewold, T.B.; Boumpas, D.T.; Goulielmos, G.N.
Abstract : Background: The vascular endothelial growth factor receptor 2 ( VEGFR2 ) gene polymorphisms have already been correlated with vascular diseases such as Coronary Heart Disease (CHD). In view of the premature atherosclerosis observed in systemic lupus erythematosus (SLE), we hypothesized that variation of VEGFR2 gene may influence endothelial function in patients with SLE. Objectives: a) To construct a three-dimensional (3D) model of the VEGFR2 regions harboring the polymorphisms rs2305948 and rs1870377, localize them on this model and explore their putative role on the VEGFR2 function in SLE; and b) To determine whether these polymorphisms are associated with risk of SLE by influencing endothelial cells. Methods: Three-dimensional (3D) homology modeling of the mutation V297I was based on the 3D structure of domains D2 and D3 of VEGFR2 in complex with VEGF-C, while mutation Q472H was investigated by homology modeling on the KIT ectodomain structure. The V297I (rs2305948) and Q472H (rs1870377) SNPs in VEGFR2 were genotyped with Taqman technology in 250 SLE patients and 241 healthy controls from a Greek population (Cretan). The replication sample set for the rs1870377 SNP consisted of 253, 184 and 77 patients with SLE of African-, European- and Hispanic-American origin, respectively, as well as geographically/ethnically-matched controls Results: Modeling revealed that polymorphism V297I affects the efficiency of trans-autophosphorylation and cell signaling while Q472H affects homotypic contacts of membrane proximal Ig-like domains. These findings prompted us to examine whether these polymorphisms contribute to SLE risk or vascular damage. No significant difference was observed in the frequency of the minor allele A of rs1870377 when SLE patients were compared with controls either in the Greek population or in the 3 replication groups analyzed. The TT genotype was found to be associated with a higher number of circulating endothelial cells (CECs) in SLE patients. Half of the Greek SLE patients enrolled in the study, with clinical data, analyzed further but no association between genotype and clinical CVD was detected. Furthermore, no association was found between rs2305948 SNP and SLE when tested in the Greek population. Conclusions: Although structural data suggest that both VEGFR2 SNPs may contribute to SLE pathogenesis by impairing cell signaling, none of the SNPs analyzed was associated with increased susceptibility to SLE. However, they still may be relevant to the vascular damage/atherosclerosis in SLE and other genetic variations in or near the VEGFR2 locus may play a role in the disease. Disclosure of Interest: None Declared